Determining of the environmental impact of sewer trenchless renewal techniques - Kuliczkowska, Emilia; Kuliczkowski, Andrzej (Instal, 2022)
Research on the impact of trenchless renewal techniques for the environment allowed determining a total of 15 multidisciplinary factors affecting atmosphere, hydrosphere, biosphere, lithosphere and antroposphere. Some of these values are measurable and others are not-measurable. A quantitative approach that can combine measurable and not-measurable factors in the decision making process has been proposed. It concerns the quantitative assessment of the environmental impact of different trenchless renewal techniques and allows them to be ranked in order from the most favourable to the least favourable in terms of their impact on the environment.
Keywords: trenchless techniques; renewal; environmental impact; evaluation criterion